The Effect of Health Information Technology on Time and Cost Saving in Remote areas of Iran - Mahdie Shojaei Baghini1, Massume Mir Nejad2, Sedisghe Shojaei Baghini3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The present study aims at investigating the effect of health information technology on time and cost saving in the perspective of users of teaching hospitals in in remote areas of Iran. This is an applied study with a descriptive-analytical and cross-sectional method conducted on users of hospitals in remote areas of Iran using stratified random sampling. Data collection instrument was a selfmade questionnaire, the face validity and reliability of which were confirmed by Cronbach’s alpha 0.94. Data were collected in person and analyzed by SPSS software V. 21 and descriptive and analytical statistics. Based on the Chi-square test results, there was a significant relationship between the effects of health information technology on time saving as well as cost saving. The results of Kruskal-Wallis test showed no significant relationship between education level, age and work experience and time and cost saving as well. User satisfaction is one of the most important aspects of the success of information systems, therefore, it is recommended that senior managers pay attention to the individual aspects of the employees working in the organization, provide them with necessary training before implementing the information systems, and involve them in the decisions in using such technologies.